Relationship Of Gardening Activities To Elderly Stress Level In Kuranji District Of Padang City - Afriyuni, Fera; Jumeno, Desto; Susanti, Lusi (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 8 No 1 (2022): Volume 8 No 1 Tahun 2022, 2022)
Aging and physical decline in the elderly due to the degenerative process causes stress for the elderly. Humans evolved from helplessness to become perfect m a n and independently, and eventually do not know what to do facing advanced age. Almost all the events can be stressful. Gardening is one of the alternatives that can reduce the stress of the elderly. This research aims to find out the effect of gardening on elderly stress. This study used purposive sampling techniques to disseminate questionnaires to as many as 237 elderly in Kuranji Sub-district of Padang City. The measuring instrument used to measure stress is PSS 10 and compares the frequency and duration of elderly gardening. The results shows that gardening with time minimum duration of 30 minutes can reduce stress and emotions, because gardening can stimulate brain chemicals that can make you happier and more relaxed. Gardening activities will make our bodies move while breathing fresh air and getting to know the environment, which will make our minds fresher. This study was tested by the Kruskal Wallis tatistical test with a value of p=0.034, with moderate stress levels and strength associated with the Spearman Rho test, with a correlation value of -0.236. This study concludes that gardening effectively changes the stress levels of the elderly, so it is expected that the elderly do gardening as one of the non-pharmacology alternatives conducted independently without causing side effects.